Efficacy and safety of aldosterone synthase inhibitors for uncontrolled hypertension: a meta-analysis of randomized controlled trials and systematic review - Gao, Yifan; Mu, Xu; Pang, Xingxue (Frontiers in Pharmacology, 2025)
BackgroundUncontrolled hypertension is a major global health concern. Aldosterone synthase inhibitors (ASIs) show promise as a new treatment approach for blood pressure management.MethodsA systematic review and meta-analysis were conducted on randomized controlled trials comparing ASIs versus placebo for uncontrolled hypertension. The search included PubMed, Cochrane Library, Web of Science, and Embase databases from inception to 7 July 2025, limited to English-language publications. Data extraction was performed independently by two authors.ResultsFour randomized controlled trials involving 1,838 patients (mean age 62 years; 47% female) were analyzed. The results demonstrated that ASIs significantly reduced office systolic blood pressure by 8.21 mmHg (95% CI, −10.64 to −5.78; P < 0.0001) and diastolic blood pressure by 3.64 mmHg (95% CI, −5.65 to −1.63; P = 0.0004). The risk ratio for adverse events was 1.42 (95% CI, 1.25-1.60; P < 0.00001), with a similar trend observed for serious adverse events (risk ratio 1.17; 95% CI, 0.63-2.17; P = 0.61). No treatment-related deaths occurred. However, ASIs were associated with a significantly higher risk of hyperkalemia (risk ratio 7.97; 95% CI, 2.27-27.99; P = 0.001).ConclusionASIs significantly lower blood pressure in hypertensive patients with an acceptable safety profile, though hyperkalemia risk requires monitoring. These results suggest ASIs may be a viable hypertension treatment, but larger studies are needed.